Performance of Multi-Well Exploitation and Reinjection in a Small-Scale Shallow Geothermal Reservoir in Huailai County - Yuan, Wenzhen; Zhang, Dailei; Zhang, Yi; Gao, Jun; Liu, Tongzhe; Zhai, Haizhen; Jin, Guangrong; Wang, Guiling; Zhang, Baojian (Frontiers in Earth Science, 2021)
The sustainable development of a shallow aquifer geothermal reservoir is strongly affected by the reinjection–production strategy. However, the reinjection–production strategy optimization of a small-scale exploitation unit with tens of meters of well spacing is site specific and has not yet been fulfilled. This study numerically investigates sustainable heat extraction based on various reinjection–production strategies which were conducted in a single-phase aquitard–aquifer geothermal system in Huailai County, Hebei Province, China. The response of the water level and production temperature is mainly discussed. The numerical results show that production without reinjection induces the highest production temperature and also the water level drawdown. Although reinjection in a single doublet well system is conducive to the control of water level drawdown, the introduction of the thermal breakthrough problem causes a decrease in the production temperature. The thermal breakthrough and sustainability of geothermal reservoirs highly depend on the well spacing between the production and reinjection wells, especially for the small-scale field. Therefore, a large well spacing is suggested. A multi-well system facilitates the control of water level drawdown while bringing intensive well interference and thermal breakthrough. Large spacing between the production and reinjection wells is also the basic principle for the design of the multi-well system. A decrease in openhole length leads to an increase in the production temperature and output thermal power. An increase in the production rate affects the thermal breakthrough highly and shortens the lifetime of the geothermal system. Furthermore, the extracted thermal energy is highly affected by the reduction in the reinjection temperature. The results in this study can provide references to achieve sustainable geothermal exploitation in small-scale geothermal reservoirs.